The effect of zoledronic acid on the fracture risk in men with osteoporosis - Spiegel, Rainer Christian; Nawroth, Peter Paul; Kasperk, Christian (Journal of endocrinological investigation, 2014)
Prospective, placebo-controlled, double-blind, randomized studies on osteoporosis treatment with bisphosphonates in men are rare. This review focuses on a recent trial and compares the results with other studies.